ANTIHYPERURICEMIA SCREENING OF Mimosa pudica L. HERB EXTRACT THROUGH ITS ANALGESICS AND ANTIINFLAMMATORY ACTIVITY ASSAY - Sumiwi, S.A -; Susilawati_Y -; Muhtadi, A -; Abdassah, M -; Subarnas, A - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2014)
Traditionally, herbs of Mimosa pudica L. are being usedto treat insomnia, hematuria, inflammation, emesis,dismenorrhoea, menorrhagia, arthritis rhematoid, convultion,depresion, and diabetes. Previous in vitro studyshowed that herbs extract of Mimosa pudica L inhibiteduric acid formation via xanthine oxidase inhibition of82.11 and 62.10% for concentration of 125 and 62.5 μg/mL, respectively. Hyperuricemia is indicated by pain andoedema which are the symptoms of inflammation. This invivo study was perfor-med to screen antihyperuricemiaactivity of herbs extract of Mimosa pudica L throughanalgesic and antiinflammatory assays on mice.Analgesic activity of Mimosa pudica L herb extract atdosage of 125, 250 and 500 mg/kg of body weight wasobserved on mice using writhing reflex method withacetic acid 0,07 % as inducer. The results showed thatall three dosages inhibited pain at the percentage of9.58, 45.35, and 60.28% respectively. Antiinflammatoryactivity assay was done using carageenan-induced pawedema method on white male rats. Dosages used were250, 500 and 1000 mg/kg of body weight. The resultsshowed that all three dosages inhibited edema at thepercentages of 35.20, 42.74, and 51.10% respectively. It isconcluded that herbs extract of Mimosa pudica L can beproposed as an antihyperuricemia.Keywords: Antihyperuricemia, Analgesic, Anti-inflammatory,Mimosa pudica L.